The genus Odontepyris Kieffer (Hymenoptera, Bethylidae) from China - Wang, Chung-Hong; He, Jun-Hua; Chen, Xue-Xin (Zootaxa, 2021)
Ten new species of Odontepyris Kieffer from China are described and illustrated: O. angustus sp. nov., O. ecarinatus sp. nov., O. eminens sp. nov., O. flavipedis sp. nov., O. hirtus sp. nov., O. latifrontalis sp. nov., O. occiputalis sp. nov., O. xiaoi sp. nov., O. xui sp. nov., and O. yunnanensis sp. nov.. A key to the known Chinese species is provided.